2020
DOI: 10.1093/ejcts/ezaa053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of permanent pacemaker implantation after conventional aortic valve replacement—a propensity-matched analysis in patients with a bicuspid or tricuspid aortic valve: a benchmark for transcatheter aortic valve replacement

Abstract: OBJECTIVES Elective treatment of aortic valve disease by transcatheter aortic valve replacement (TAVR) is becoming increasingly popular, even in patients with low risk and intermediate risk. Even patients with a bicuspid aortic valve (BAV) are increasingly considered eligible for TAVR. Permanent pacemaker implantation (PMI) is a known—frequently understated—complication of TAVR affecting 9–15% of TAVR patients with a potentially significant impact on longevity and quality of life. BAV patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
3
12
3
Order By: Relevance
“…Specifically, our study found no difference in the rate of complete heart block or need for pacemaker implantation after stentless AVR in both the BAV and TAV groups. This differs from the findings of a recent study by Haunschild and colleagues, 4 who reported a higher pacemaker implantation rate in BAV patients compared with TAV patients (5.1% vs 4.4%) after isolated AVR with a bioprosthesis (86%) or mechanical valve (14%) for aortic stenosis. 4 Interestingly, the surgical technique was modified aortic root implantation for all of our patients, and the pacemaker implantation rate of 2.1% in the BAV group is lower than the rate reported by Haunschild and colleagues (5.1%), whereas our pacemaker implantation rate in TAV patients was similar to the rate reported in that study (3.6% vs 4.4%).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Specifically, our study found no difference in the rate of complete heart block or need for pacemaker implantation after stentless AVR in both the BAV and TAV groups. This differs from the findings of a recent study by Haunschild and colleagues, 4 who reported a higher pacemaker implantation rate in BAV patients compared with TAV patients (5.1% vs 4.4%) after isolated AVR with a bioprosthesis (86%) or mechanical valve (14%) for aortic stenosis. 4 Interestingly, the surgical technique was modified aortic root implantation for all of our patients, and the pacemaker implantation rate of 2.1% in the BAV group is lower than the rate reported by Haunschild and colleagues (5.1%), whereas our pacemaker implantation rate in TAV patients was similar to the rate reported in that study (3.6% vs 4.4%).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are consistent with the findings reported from 2 studies of matched BAV and TAV patients with isolated AVR. 4,7 Both of those studies and our present study showed better Kaplan-Meier survival in BAV patients and similar The underlying mechanisms for better long-term survival in BAV patients after stentless valve implantation is unclear. The BAV develops calcification and aortic stenosis owing to the intrinsic anatomy of the valve.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The existing literature suggests that despite improvements in valve design over multiple generations, permanent pacemaker implantation (PPMI) is required in 9-15% of cases following TAVR, a significantly higher risk than in patients undergoing SAVR. [21][22][23] Importantly, implantation of a permanent pacemaker following TAVR is associated with longer hospital and intensive care unit (ICU) stays, increased overall cost, risk of heart failure, and rehospitalization. 24,25 Independent predictors of PPMI in previous reports have included preexisting conduction abnormalities, implant depth, and need for repositioning of self-expanding implants.…”
Section: Discussionmentioning
confidence: 99%
“…Most of this transient pacing requirement resolves on its own but it has also been shown to be associated with higher risk of the need for long-term pacing. [ 12 , 26 ] Patients suspected to be in need of temporary pacing after the TAVR procedure should be considered for an internal jugular approach for the temporary pacing wire. This can improve patient comfort as observation periods with temporary pacing wires in place can go extend to 48 hours.…”
Section: Timing Of Heart Blockmentioning
confidence: 99%